DD-007 Contribution of electronic prescriptions on time management at the hospital pharmacy. (25th February 2017) - Cheikh, A; Mefetah, H; Rahali, Y; Bouatia, M
Abstract : Background: Medicines prescription is the centrepiece in the triad of care (patient–prescriber–pharmacy). The electronic prescription has long been considered an effective means to reduce transcription errors as well as securing the flow of drugs at the hospital level. However, the experience of the Massachusetts General Hospital of Boston team found an error rate comparable between manual and electronic prescriptions (11.7%) 1 What about the time saving that electronic prescribing can provide compared with manual prescribing? Purpose: The objective of this work was to evaluate the impact of electronic prescription of medicine on time saving of the pharmaceutical team compared with manual prescription in our hospital. Material and methods: We analysed the prescriptions received and processed in our hospital pharmacy over a period of 1 month according to good dispensing practices. We calculated the time between receipt of prescriptions and dispensation of medicines by the pharmaceutical team for both prescription modalities (electronic and manual). Results: 384 (58%) manual prescriptions and 276 (42%) electronic prescriptions were analysed, prepared and dispensed by the pharmacy team in our hospital. The average length of preparation of manual prescriptions was 25±10 min and the average length of preparation of electronic prescriptions was 15 min±5. The difference was statistically significant (p<0.001). The number of drugs dispensed by prescription is more important for electronic prescriptions (2.2 vs 1.8 (p=0.005)). Conclusion: Our team found a considerable gain in time (10 min by prescription or 170 min per day) between prescription of medicines by physicians and their dispensation by the hospital pharmacy despite the high number of drugs dispensed in the case of electronic prescriptions. This time saved would allow the pharmaceutical team to focus on other activities, more precisely the pharmacological analysis of prescriptions and hospital preparations. References and/or acknowledgements: 1. Nanji KC, Rothschild JM, Salzberg C, et al. Errors associated with outpatient computerised prescribing systems. J Am Med Inform Assoc2011;18:767–73. No conflict of interest